Physical performance, technical activity and injury risk in a professional soccer team in match-play over a prolonged period of fixture congestion - Lago-Penas, C.; Dellal, A.; Casais, L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Professional soccer players are often required to play competition matches with only 2-3 days` recovery. However, the effect of a prolonged period of fixture congestion on players` performance is still inconclusive. Therefore, the aim of this study was to investigate recovery via analysis of activity profiles in a professional soccer team over an intense period of matches. Methods: A computerized player tracking system (AMISCO Pro, Sport-Universal Process, Nice, France) was used to characterize activity profiles in the reference team. A 1-way repeated measures ANOVA was used to compare outcome measures in each category of physical and skill-related performance across: 1) 6 consecutive games over the 21-day-period, and; 2) games played during 3 different congested fixture periods in the same season. The methodologies and definitions of injury are similar to those employed in other investigations on elite soccer play (Carling, et al., 2011; Dupont, 2010). Results: Across the 6 successive matches, no differences were reported for the overall distance covered (p=0.072) or that covered in high-intensity (p=0.622), moderate-intensity (p=0.277), low-intensity (p=0.467) or light-intensity (p=0.368) running. No differences were found in the analysis of the technical actions. The incidence of injury across the prolonged periods was similar to that reported in matches played outside the study periods; however, injury rate during training time was significantly lower during congested period to those outside the study period (4.6 vs. 14.6 per 1000 h exposure, p<0.001). The comparison of physical performance in matches played across the 3 separate periods (August, September and October) revealed significant increases in the overall distance covered. Discussion: This study provided a valuable opportunity to study physical performance, injury risk and severity in match-play over a prolonged period of fixture congestion. Physical performance and injury rates were generally unaffected which shows that coaches, support staff and players in high-performance teams in a professional setting can cope with a congested playing calendar. As a whole, these results also lend support to findings observed other studies (Carling et al., 2011; Lago-Peñas et al, 2011; Odetoyinbo et al., 2009).